Stereotactic Body Radiotherapy for Metachronous Multisite Oligo-Recurrence: A Long-Surviving Case with Sequential Oligo-Recurrence in Four Different Organs Treated Using Locally Radical Radiotherapy and a Review of the Literature - Hiroshi Onishi; Masatoki Ozaki; Kengo Kuriyama; Takafumi Komiyama; Kan Marino; Masayuki Araya; Ryo Saito; Shinichi Aoki; Yoshiyasu Maehata; Licht Tominaga; Mitsuhiko Oguri; Iori Watanabe; et al. (Pulmonary Medicine)
Stereotactic body radiotherapy (SBRT) for oligometastases represents a recent trend in radiation oncology. While abundant data are available regarding the use of SBRT for the treatment of lung or liver oligometastases from various retrospective series and prospective trials, relatively little information has been accumulated for the treatment of oligometastases at sites other than the lungs and liver, particularly for sequential oligometastases in multiple organs. Oligometastases with primary lesions controlled is called “oligo-recurrence.” We describe herein the case of a lung cancer patient who developed repeated oligo-recurrence at multiple sites that were each controlled by radical radiotherapy and achieved long-term survival and discuss the merits of locally aggressive radiotherapy for this type of disease condition with reviewing the literature. Although further investigation should be undertaken to clarify the benefits, objectives, and methods of SBRT for the treatment of oligometastases, we believe utilization of SBRT may be worthwhile for patients with remote metastases who hope for treatment to acquire better local control and possible longer survival.